The island of mad scientists : being an excursion to the wilds of Scotland, involving many marvels of experimental invention, pirates, a heroic cat, a mechanical man and a monkey - Whitehouse, Howard (Whitehouse, Howard, 1958- Mad misadventures of Emmaline and Rubberbones., 2008)
Aviatrix Emmaline Cayley, test pilot Rubberbones and the rest of their wacky household decide to rendezvous on the Scottish island of Urgghh where they hope to find refuge. But the island is anything but safe--mad scientists inhabit the island and a villain known as the Collector, who devotes his time to kidnapping inventors, lives next-door.